Hiding Images in the Spatial Domain - Sead Almola, Sahera Abued (Informatica, 2023)
Nowadays, steganography has become a useful technology and the interest in it has increased due to the rapid growth in the use of the internet, and it is applied to transmit information secretly using various techniques. Hiding is one of the main important techniques in steganography, which is the science of hiding secure information inside the carrier body to provide secure communication via the internet, so that only the sender and receiver can identify and reveal it. In stealth, many different forms of carrier can be used such as image, video, protocol, and audio. The digital image is most commonly used as a vector file because of its frequency on the internet. There are many changing techniques of steganography, and each has strengths and weaknesses. In this study, we conducted a review of techniques used for hiding in the spatial domain to explore the term hiding by reviewing and collecting different studies related to this field published from 2015 to 2021. This study evaluated nine proposed approaches to address this problem. Three metrics - image quality, message capacity, and security - were used to evaluate each method. Finally, the results are presented and summarized, since the capacity and quality of the hiding image are important for a good approach. There is a trade-off between the amount of confidential data that can be included, image distortion, and the security of image hiding. The disadvantages of each method are also identified, which serve as the basis for future research. Along with a complete review of the basic concepts of steganography additionally, types of steganography and interest in image steganography based on spatial domain are presented. Furthermore, the criteria most commonly used to evaluate steganography performance in terms of non-perception, payload capacity, and robustness are addressed. Each spatial domain technology attempts to meet the most important steganographic design requirements of (1) maintaining non-perception at a good level, (2) high capacity payload, and (3) robustness against intruder attacks. But in truth, the perfect steganography system does not exist, and it may be another lacking in robustness. for example ,It has a high ability but suffers from lack of resistance to statistical attacks. Therefore, when designing an LSB hiding scheme file a balance must be struck between the requirements for hiding information. A good recommendation from the techniques reviewed is that the combination of steganography and encryption techniques increases the confidentiality of the hidden message.